1999
DOI: 10.1200/jco.1999.17.10.3201
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of the Standardized Uptake Value on 18F-Fluoro-2-Deoxy-Glucose–Positron Emission Tomography Scan in Non–Small-Cell Lung Cancer: An Analysis of 125 Cases

Abstract: We conclude that the FDG uptake in primary NSCLC on PET has an important prognostic value and could be complementary to other well-known factors in the decision on adjuvant treatment protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
238
5
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(262 citation statements)
references
References 15 publications
14
238
5
5
Order By: Relevance
“…It is not surprising therefore that the present results mirror those for lung cancer, where SUV has proved to be a significant prognostic indicator (Ahuja et al, 1998;Saunders et al, 1999;Vansteenkiste et al, 1999). Vansteenkiste et al (1999) suggested a SUV of seven, and Ahuja et al (1998) one of 10 as a cut-off value that distinguishes good and bad prognostic groups, although there is probably a range of 6 -11 where prognosis deteriorates. Previous studies in head and neck cancer have found SUV important in differentiating benign and malignant disease but were unable to define a cut-off value (Nowak et al, 1999).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is not surprising therefore that the present results mirror those for lung cancer, where SUV has proved to be a significant prognostic indicator (Ahuja et al, 1998;Saunders et al, 1999;Vansteenkiste et al, 1999). Vansteenkiste et al (1999) suggested a SUV of seven, and Ahuja et al (1998) one of 10 as a cut-off value that distinguishes good and bad prognostic groups, although there is probably a range of 6 -11 where prognosis deteriorates. Previous studies in head and neck cancer have found SUV important in differentiating benign and malignant disease but were unable to define a cut-off value (Nowak et al, 1999).…”
Section: Discussionsupporting
confidence: 72%
“…Firstly, most patients with advanced disease present with large tumours, and FDG uptake may simply reflect the larger tumour burden in these patients. Indeed some of the lung studies have shown that size as well as SUV has prognostic value (Saunders et al, 1999;Vansteenkiste et al, 1999). However in the current study increasing tumour diameter had little effect on FDG uptake (SUV), suggesting that tumour burden alone cannot account for these findings.…”
Section: Discussioncontrasting
confidence: 66%
“…Several studies have shown that high glucose uptake or Glut-1 expression predicts poor prognosis and that Glut-1 levels often are elevated in 18F-FDG-avid tumors, [30][31][32][33][34][35][36][37][38][39][40][41] but their regional or microregional spatial association has seldom been studied and remains unclear. Our colocalization analysis of 18 F-FDG uptake and Glut-1 expression shows some, albeit weak, spatial linkage and again the strongest correlation was observed in the relatively nonglycolytic tumor model (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT provides quantitative data on the level of metabolic activity by calculating the degree of F-18 FDG uptake, known as the standardized uptake value (SUV). PET/CT also has been suggested to have a considerable prognostic utility in various cancers [10][11][12][13]. In a previous study, primary tumor maximum SUV (pSUVmax) exhibited a strong relationship to known prognostic parameters of invasive ductal cancer (IDC) of the breast and could be used as a good surrogate marker for the prediction of progression in patients with IDC [14].…”
Section: Originalmentioning
confidence: 99%